Earnings management and corporate finance : the importance of transparent financial reporting - Lizińska, Joanna; Remlein, Marzena; Czapiewski, Leszek (Routledge, 2025)
"In today's dynamic landscape of accounting, corporate finance, and business management, earnings management has assumed paramount importance. Transparent and reliable accounting information is crucial for accurate corporate performance forecasting and financial decision-making. This book uniquely discusses practical earnings management methods within the accounting and taxation realms. It is supported by extensive international evidence linking informativeness of financial reports to companies' financial decisions. Delving into the earnings management process, this book provides profound insights into how profits can be influenced through accounting choices and real business transactions. Real-life case studies will undoubtedly facilitate the understanding of accounting and taxation methods. Additionally, it unravels key elements of corporate finance puzzles related to the transparency of financial reports, including the macroeconomic environment, profit thresholds, cash management, audit quality, financing decisions, and financial health. With broad empirical evidence from various European countries, it multidimensionally explores the important link between the quality of information in financial statements and trade-offs behind financial decisions. The book serves as a valuable reference for international researchers in corporate finance, accounting, and corporate governance. It is also a powerful tool for business practitioners, including owners, lenders, auditors, regulatory and professional bodies, business partners, or other market participants. For those seeking the latest insights on earnings management, those producing or assessing accounting information, and those using financial reports in their research or business practice, this book is a must-read"-- Provided by publisher.
Keywords: Corporations -- Finance.; Finance -- Decision making.; Industrial management.; elektronické knihy; electronic books